SOCIO-ECONOMIC AND CULTURAL FACTORS OF THE COMMUNITY TOWARDS THE NUTRITIONAL STATUS OF CHILDREN UNDER FIVE (HEALTH STUDIES IN COASTAL AREAS OF BIREUN REGENCY) - Yusrizal, (Indonesian Journal of Medical Anthropology, 2022)
This study discusses survey research using explantory research methods (explanations) that look for how much influence socio-economic and cultural factors of the community on the nutritional status of children under five in the Coastal Area of Bireuen Regency. The purpose of the study was to analyze the influence of socioeconomic factors consisting of: education, employment, income, number of family members, and cultural factors of society i.e. knowledge, diet, abstinence food, distribution of food in the family. The results of the study showed that the effect on the nutritional status of children under five in the coastal area of Bireuen Regency was the level of knowledge (B = 0.260). Variables that had no effect in the study were income, number of family members, abstinence food and distribution of food in the family